Applying fuel cells to data centers for power and cogeneration - Carlson, Amy L. (Kansas State University, 2009)
Data center space and power densities are increasing as today’s society becomes more dependent on computer systems for processing and storing data. Most existing data centers were designed with a power density between 40 and 70 watts per square foot (W/SF), while new facilities require up to 200W/SF. Because increased power loads, and consequently cooling loads, are unable to be met in existing facilities, new data centers need to be built. Building new data centers gives owners the opportunity to explore more energy efficient options in order to reduce costs. Fuel cells are such an option, opposed to the typical electric grid connection with UPS and generator for backup power. Fuel cells are able to supply primary power with backup power provided by generators and/or the electric grid. Secondary power could also be supplied to servers from rack mounted fuel cells. Another application that can benefit from fuel cells is the HVAC system. Steam or high-temperature water generated from the fuel cell can serve absorption chillers for a combined heat and power (CHP) system. Using the waste heat for a CHP system, the efficiency of a fuel cell system can reach up to 90%. Supplying power alone, a fuel cell is between 35 and 60% efficient. Data centers are an ideal candidate for a CHP application since they have constant power and cooling loads. Fuel cells are a relatively new technology to be applied to commercial buildings. They offer a number of advantages, such as low emissions, quiet operation, and high reliability. The drawbacks of a fuel cell system include high initial cost, limited lifetime of the fuel cell stacks, and a relatively unknown failure mode. Advances in engineering and materials used, as well as higher production levels, need to occur for prices to decrease. However, there are several incentive programs that can decrease the initial investment. With a prediction that nearly 75% of all 10 year old data centers will need to be replaced, it is recommended that electrical and HVAC designer engineers become knowledgeable about fuel cells and how they can be applied to these high demand facilities.
Keywords: fuel cell; cogeneration; combined heat and power; data center; Engineering, General (0537)